2009
DOI: 10.1007/s00726-009-0367-z
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of allosteric conformations and homocarnosine concentration on carnosinase activity

Abstract: Activity of carnosinase (CN1), the only dipeptidase with substrate specificity for carnosine or homocarnosine, varies greatly between individuals but increases clearly and significantly with age. Surprisingly, the lower CN1 activity in children is not reflected by differences in CN1 protein concentrations. CN1 is present in different allosteric conformations in children and adults since all sera obtained from children but not from adults were positive in ELISA and addition of DTT to the latter sera increased O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 33 publications
5
48
0
Order By: Relevance
“…In addition to (CTG) n polymorphism in the CNDP1 gene (10,16,24), the female sex (6,10,29) and increasing age (29) are determinants associated with higher carnosinase activity that cannot be manipulated. In vitro experiments, however, revealed that activity of the carnosinase enzyme was markedly decreased in the presence of both homocarnosine (␥-aminobutyryl-L-histidine) (28,29) and anserine (␤-alanyl-N 1 -methylhistidine) (28). However, the correlation between circulating homocarnosine or anserine levels in fasted subjects and plasma carnosinase activity in vivo is less obvious (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to (CTG) n polymorphism in the CNDP1 gene (10,16,24), the female sex (6,10,29) and increasing age (29) are determinants associated with higher carnosinase activity that cannot be manipulated. In vitro experiments, however, revealed that activity of the carnosinase enzyme was markedly decreased in the presence of both homocarnosine (␥-aminobutyryl-L-histidine) (28,29) and anserine (␤-alanyl-N 1 -methylhistidine) (28). However, the correlation between circulating homocarnosine or anserine levels in fasted subjects and plasma carnosinase activity in vivo is less obvious (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments, however, revealed that activity of the carnosinase enzyme was markedly decreased in the presence of both homocarnosine (␥-aminobutyryl-L-histidine) (28,29) and anserine (␤-alanyl-N 1 -methylhistidine) (28). However, the correlation between circulating homocarnosine or anserine levels in fasted subjects and plasma carnosinase activity in vivo is less obvious (28,29). Importantly, a good glycemic control, either by intervention with insulin, exercise, or diet, seems to be crucial for diabetic patients as this not only directly influences oxidative and glycation stress but also indirectly affects carnosinase activity (31).…”
Section: Discussionmentioning
confidence: 99%
“…Separation was performed by liquid chromatography according to the method previously described (Peters et al 2010).…”
Section: Carnosine Concentrationmentioning
confidence: 99%
“…into their constituent amino acids, with the highest specificity for carnosine (28,29). Both human genetic association studies and animal models suggest a pivotal role for the carnosinecarnosinase system in microvascular complications of diabetes (3,19,33,34,40).…”
mentioning
confidence: 99%
“…In healthy subjects, sex, age, and particular polymorphisms of CNDP1 are known determinants of plasma carnosinase activity (12,22,29). In one study with diabetic patients (type 1 and 2), carnosinase activity was increased compared with genotype-matched healthy controls (32).…”
mentioning
confidence: 99%